If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-12=8(x-1.5)
We move all terms to the left:
8x-12-(8(x-1.5))=0
We calculate terms in parentheses: -(8(x-1.5)), so:We get rid of parentheses
8(x-1.5)
We multiply parentheses
8x-12
Back to the equation:
-(8x-12)
8x-8x+12-12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 4-3(2x+1)=14 | | 3(9x+1)-1=29 | | 12x−7=21 | | 4x-9=12(1/3x-3/4) | | 5x=6x-x | | 4.6g+8=1.6g+20 | | 1/17x+3=15 | | 1/17x+3=15 | | 3(4x+5)=14x+10-2x+5 | | 56=14g | | 30=-3y+6(y+3) | | 7p2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | (8x)^2=8x^2 | | 7x−8=5x−16 | | 25=45-x | | 9(2m-)=18m-81 | | 7-2y/2-2/5(2-y)=1/1/4 | | 4u-8+2(2u+4)=-6(u+3) | | `8+4x=-10+x | | 4u-8+2(2u+4)=-6(u+3) | | -6+2v=2 | | 4(u+4)=-6u-24 | | 8x(X-2)=96 | | t+58=75 | | Y+6=3(x+1) |